KNOWLEDGE IMPROVEMENT OF YOUTH ABOUT THE IMPACT OF PROMISCUITY - Meli Diana; Elvira Bella Chinthia; Riscahyani Sartika Ningrum; Nurul Jannah; Fifiyanti Yosefina (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2021)
Health promotion activities regarding the impact of promiscuity in MTs. Islamiyah Tanggulangin Sidoarjo is a form of community service in the form of counseling aimed at increasing children's knowledge about the impacts and dangers of promiscuity which are increasingly prevalent among teenagers today. The implementation of these activities on December 14, 2019 took place at MTs. Islamiyah Tanggulangin Sidoarjo. With the target is MTs students. Islamiyah Tanggulangin Sidoarjo. Prior to the implementation of these activities, there was a process of preparing activities for approximately 2 weeks before the activities were carried out, starting from determining the theme of the extension to applying for permits to the parties concerned. As a form of evaluation, this activity was attended by 76 students from grade VII to grade IX, participants joined the activity happily and looked very enthusiastic, health promotion activities could run on time and smoothly.